Pregnancy outcomes in nulliparous women after ultrasound ablation of uterine fibroids: A single-central retrospective study - Jun shu Li (Nature Portfolio, 2017)
Abstract To explore the impact of high-intensity focused ultrasound (HIFU) ablation of uterine fibroids in nulliparous women on subsequent pregnancy and delivery. A retrospective analysis was conducted of nulliparous women who received HIFU treatment at Chongqing Medical University, Chongqing,China, from January 1, 2010, to January 1, 2015. A total of 189 cases were enrolled, the median follow-up time was three years. Among them,there were 131 cases pregnancy with a total of 133 times,the pregnancy rate was 69.3% (131/189),and the spontaneous conception rate was 95.4% (125/131). Of 131 pregnant women, 19 were on-going pregnancy, terminated pregnancy 114 times,which include 93 times successfully delivery with a 76.3% (87/114) full-term birth rate,and the cesarean section rate was 72.0% (67/93). Of 94 newborns,the average birth weight was (3.3 ± 0.4)kg (range:1.5–4.8 kg), and a pair of them were identical twins. The incidence of complications during pregnancy and delivery were 10.8% (10/93) and 7.5% (7/93),respectively,except one woman failed on-going pregnancy and one woman suffered hysterectomy due to the complications,others all successful pregnant and delivered. Multiple-factor regression analysis found that age and infertility history were the important factors that may affect pregnancy after HIFU (P < 0.01). Nulliparous women who undergo HIFU treatment for uterine fibroids can subsequently have successful pregnancy and delivery safely.